El modelo pedagógico constructivista en el aprendizaje significativo de la asignatura de ciencias naturales de los niños y niñas del séptimo año de educación básica de la Escuela “Rafael J. Bazante” cantón San José de Chimbo provincia Bolívar periodo 2011 - 2012 - Analuiza García, Cruz Aurora (2012)
The present work has titled it “THE PEDAGOGIC PATTERN CONSTRUCTIVISTA FOR THE LEARNING SIGNFICATIVO OF CHILDREN AND GIRLS OF SEVENTH YEAR OF BASIC EDUCATION OF THE SCHOOL “RAFAEL J. BAZANTE” CANTON SAN JOSÉ DE CHIMBO COUNTY BOLIVAR PERIOD 2011-2012.” This investigation carries out it with the collection of data based on those (those) Students, Teachers and Parents of Family of the School Rafael J. Bazante. To complete this objective it is necessary to carry out a shop for the Educational ones and the heady results will be taken into account, for the elaboration of the proposal with their due summations and recommendations achieving this way an education of quality. I put to your consideration since the importance that should be given to the Model Pedagogic constructivist for the significant learning in those and the students, the results of the analyses they confirm the validity of the hypothesis proposed in this investigation. In the theoretical Marco the scientific information the same one is sustained that will serve for reference to conquer all type of difficulties that you/they are presented in the seventh year-old students. The present thesis was elaborated observing each one of the lines of the investigation minutely presently topic, I demonstrated this way it in the present investigation the necessity of the application of an appropriate, bony pedagogic model the Pedagogic Model Constructivist. At the present time the desire exists of getting a better life and this was only achieved with the simple one made of educating the children of the School Rafael J. Bazante with an education of efficient, effective and he/she will give an effective education as a result.